Perfiles y trayectorias delictivas a la cárcel. Una agenda de investigación - Ramírez de Garay, Luis David (El Colegio de México, 2017)
Prisons are a black box in the Mexican justice system. The systemic lack of transparency and public information has derived in an absence of reliable statistical information and academic research.  A key element to throw some light around prisons is the study of the trajectories and social paths followed by inmates previous to incarceration. In criminology, the Life-Course Perspective (LCP) offers a wide array of theoretical and methodological resources to study these aspects of incarcerated population. This note shows how the LCP is useful to study these characteristics for two subgroups: young offenders and adult recidivists. At the same time, we use the opportunity to present a new line of research and its more recent research project: “Criminal Profiles and Trajectories to prison”.